Tetrakis(4-methoxyanilinium) hexachloridobismuthate(III) chloride monohydrate - Ming-Liang Liu (Acta Crystallographica Section E, 2012)
In the crystal of the title compound, (C7H10NO)4[BiCl6]Cl·H2O, the BiIII cation is located on an inversion center and coordinated by six Cl− anions in a slightly distorted octahedral geometry; the uncoordinated Cl− anion and lattice water molecule are located on a twofold rotation axis. Two independent 4-methoxyanilinium cations are linked to the Bi complex, the uncoordinated Cl− anion and lattice water molecule via N—H...Cl and N—H...O hydrogen bonds.